(untitled) (Eurasian Journal of Learning and Academic Teaching, 2024)
One of the important principles that have been declared many times in the constitution of countries is the rule of law. Legal rules mean that government officials are always obliged to apply laws and regulations in their actions and activities. Based on this principle, government activities and all forces are under the supervision and rule of law. The establishment and implementation of laws that are incomplete in form and content make the way of governance difficult. A law that is against the culture and habit of the society and the religion of the country’s citizens will never reach the government. Assessment and rooting of legal violations should be developed in the legal framework. Identifying the causes and factors of the difficulty of the rule of law and improving the quality of the laws and its ultimate goal will help to apply the law and good governance. The difficulties and challenges of implementing relevant laws have been identified, and political and legal solutions for the rule of law and solving problems have been presented. This article is based on introducing the knowledge of the rule of law and mentioning examples of ineffective laws, while also explaining the difficulties of Afghanistan’s laws. The findings indicate that the speed and multiplicity of low-quality laws and the creation of laws that do not comply with the rules of legislation and publication have brought irreparable costs, made it difficult for citizens to obey the law, and caused losses. Brought a lot the method of this research is descriptive and library.